Odontological analysis of Polish children with unilateral cleft lip and palate - Sękowski, Piotr; Żądzińska, Elżbieta; Pawłowska, Elżbieta; Sitek, Aneta; Antoszewski, Bogusław (Anthropological Review, 2019)
Tooth size, being the effect of interaction of genetic and prenatal factors, could be of importance in interpreting the multifactor causes of cleft lip/palate. Publications indicating decreased tooth parameters, no dental differences, or larger dimensions of teeth in cleft lip/palate patients. Researchers report mostly mesiodistal (MD) measurements of maxillary (affected) teeth. There is a lack of data for buccolingual (BL) diameters. Both MD and BL parameters have influence on the planning and performance of orthodontic treatment. The aim of this paper was to assess differences in mesiodistal and buccolingual tooth dimensions in Polish children with unilateral cleft lip and palate (UCLP) in comparison to patients without oral clefts. A total of 1883 permanent teeth, 1182 teeth of UCLP patients and 701 teeth of healthy participants were analyzed. Tooth diameters were performed using an orthodontic cast of dentition with a digital odontometer. The greatest anomalies were found in both maxillary canines and consisted of their reduced mesiodistal dimension and increased buccolingual dimension, resulting in a pathologically high crown shape index (BL/MD). Conclusion can be drawn that unilateral cleft lip and palate is a condition that causes morphological disturbances of varying severity in most mandibular and maxillary teeth both on the cleft and non-cleft sides.